2008
DOI: 10.1371/journal.pgen.1000179
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Modifiers of MeCP2 Function in Drosophila

Abstract: The levels of methyl-CpG–binding protein 2 (MeCP2) are critical for normal post-natal development and function of the nervous system. Loss of function of MeCP2, a transcriptional regulator involved in chromatin remodeling, causes classic Rett syndrome (RTT) as well as other related conditions characterized by autism, learning disabilities, or mental retardation. Increased dosage of MeCP2 also leads to clinically similar neurological disorders and mental retardation. To identify molecular mechanisms capable of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
80
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(83 citation statements)
references
References 58 publications
3
80
0
Order By: Relevance
“…In this model, formation of additional veins on the L3, -4 and -5 vasculature were observed (Fig. 1E), and these results were consistent with a previous report (Cukier et al, 2008). In addition, when hMeCP2 was expressed in the whole body under da-Gal4 driver, larval growth was inhibited (data not shown) and the individual died accompanied by melanization in the caudal region at the moment of pupariation (180 h after egg laying) at 25°C (Fig.…”
Section: Binding Of Human Mecp2 To Drosophila Chromatinsupporting
confidence: 92%
See 2 more Smart Citations
“…In this model, formation of additional veins on the L3, -4 and -5 vasculature were observed (Fig. 1E), and these results were consistent with a previous report (Cukier et al, 2008). In addition, when hMeCP2 was expressed in the whole body under da-Gal4 driver, larval growth was inhibited (data not shown) and the individual died accompanied by melanization in the caudal region at the moment of pupariation (180 h after egg laying) at 25°C (Fig.…”
Section: Binding Of Human Mecp2 To Drosophila Chromatinsupporting
confidence: 92%
“…The chromatin remodeling factors are conserved in Drosophila and mammal (Ho and Crabtree, 2011), although Drosophila has a different methylation site compared to mammals (Marhold et al, 2004), and the ortholog of MeCP2 has not been reported to exist in Drosophila. hMeCP2 protein was reported to genetically interact with several Drosophila chromatin remodeling factors, such as Additional sex combs (Asx), osa, pebble (pbl), and trithorax (trx) (Cukier et al, 2008). Therefore, our data suggest the possibility that hMeCP2 regulates stem cell proliferation via the modulation or/and interaction of chromatin remodeling factors independent with binding to methylated DNA.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…These experimental results are unanticipated but not unprecedented. MeCP2 has also been distinguished with the expression of gene activity, furthermore raising the intriguing possibility of a multifunctional role for MeCP2 (Cukier et al, 2008). These studies present a complicated and even contradictory set of experimental data on the binding preferences for MeCP2 and its regulatory roles in transcription (Weitzel et The MeCP2 molecule has only a 2-3-fold preference for methylated over unmethylated sequences (Hite et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…The existing literature suggests a multifunctional role for MeCP2 in regulating gene activity. These recent studies have also brought to light additional experimental information and the intriguing possibility that the MeCP2 regulatory complex could be involved in the repression of unmethylated genes (Cukier et al, 2008). In view of these observations, the emerging picture is one of remarkable complexity for MeCP2.…”
Section: Slc6a2 Promoter Is Hypomethylatedmentioning
confidence: 95%